2023
DOI: 10.5006/4289
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into Al-Zn, Mg, and Al-Mg-Rich Primer Design for Enhanced Cathodic Prevention on Sensitized Al-Mg Alloys

Abstract: Three Al-Zn, Mg, and Mg-Al rich primers (RP) were evaluated for their ability to suppress intergranular corrosion (IGC) and intergranular stress corrosion cracking (IG-SCC) on highly sensitized aluminum alloy 5456-H116 by sacrificial anode based cathodic prevention and chemical deposition effects. Tests were conducted in 0.6 M NaCl solution under full immersion. These evaluations considered the ability of the primer to attain an intermediate open circuit potential such that the galvanic couple potential with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…It should be also noted that magnesium as a pure metal is not resistant under low salinity conditions or at high pH [51]. Research conducted by other authors [52] has shown that when magnesium is in the matrix of less reactive metals, it is the main element to be depleted. In contrast, aluminium shows high stability in the pH range of 4-9 [53]; its primary corrosion products are aluminium oxides and hydroxides.…”
Section: Electrochemical Analysismentioning
confidence: 96%
“…It should be also noted that magnesium as a pure metal is not resistant under low salinity conditions or at high pH [51]. Research conducted by other authors [52] has shown that when magnesium is in the matrix of less reactive metals, it is the main element to be depleted. In contrast, aluminium shows high stability in the pH range of 4-9 [53]; its primary corrosion products are aluminium oxides and hydroxides.…”
Section: Electrochemical Analysismentioning
confidence: 96%